Prevalence of hepatitis C virus in Brazil’s inmate population: a systematic review - Magri, Mariana Cavalheiro; Ibrahim, Karim Yaqub; Pinto, Walkyria Pereira; França, Francisco Oscar de Siqueira; Bernardo, Wanderley Marques; Tengan, Fátima Mitiko (Revista de Saúde Pública, 2015)
OBJECTIVE To estimate the prevalence of hepatitis C virus infection in Brazil’s inmate population. METHODS Systematic review on hepatitis C virus infection in the inmate population. Brazilian studies published from January 1, 1989 to February 20, 2014 were evaluated. The methodological quality of the studies was assessed using a scale of 0 to 8 points. RESULTS Eleven eligible studies were analyzed and provided data on hepatitis C virus infection among 4,375 inmates from seven states of Brazil, with a mean quality classification of 7.4. The overall hepatitis C virus prevalence among Brazilian inmates was 13.6% (ranging from 1.0% to 41.0%, depending on the study). The chances of inmates being seropositive for hepatitis C virus in the states of Minas Gerais (MG), Sergipe (SE), Mato Grosso do Sul (MS), Rio Grande do Sul (RS), Goiás (GO) and Espirito Santo (ES) were 84.0% (95%CI 0.06;0.45), 92.0% (95%CI 0.04;0.13), 88.0% (95%CI 0.09;0.18), 74.0% (95%CI 0.16;0.42), 84.0% (95%CI 0.08;0.31) and 89.0% (95%CI 0.01;0.05) respectively, lower than that observed in the Sao Paulo state (seroprevalence of 29.3%). The four studies conducted in the city of Sao Paulo revealed a lower prevalence in more recent studies compared to older ones. CONCLUSIONS The highest prevalence of hepatitis C virus infection in Brazil’s inmate population was found in Sao Paulo, which may reflect the urban diversity of the country. Despite Brazilian studies having good methodological quality to evaluate the prevalence of the hepatitis C virus, they are scarce and lack data on risk factors associated with this infection, which could support decisions on prevention and implementation of public health policies for Brazilian prisons.